2021
DOI: 10.12669/pjms.37.5.4177
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the COVID-19 pandemic: Perspectives of medical students

Abstract: Objective: The objective of the study was to assess the impacts of the COVID-19 pandemic on the mental health and lifestyle of our medical students. Methods: This observational study was conducted on medical students of Shifa College of Medicine, Islamabad from June to August 2020. The GAD-7 and PHQ-9 questionnaires were used for anxiety and depression assessment. Different aspects of changes in lifestyle were evaluated and students were inquired about their views regarding the COVID-19 pandemic. The chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
(49 reference statements)
1
4
0
4
Order By: Relevance
“…A recent study about the COVID impact from the same institute revealed that almost 60% of students agreed that they had more time to study. 15 A similar trend has been observed in the literature reporting students’ performance in higher studies. 16 …”
Section: Discussionsupporting
confidence: 82%
“…A recent study about the COVID impact from the same institute revealed that almost 60% of students agreed that they had more time to study. 15 A similar trend has been observed in the literature reporting students’ performance in higher studies. 16 …”
Section: Discussionsupporting
confidence: 82%
“…Table 1 shows the overall characteristics of the 41 included studies ( Elhadi et al, 2020 ; Jindal et al, 2020 ; Liu et al, 2020 ; Medeiros et al, 2020 ; Muhammad Alfareed Zafar et al, 2020 ; Nadeem et al, 2020 ; Nakhostin-Ansari et al, 2020 ; Nihmath Nisha et al, 2020 ; Sartorao Filho Carlos et al, 2020 ; Sun et al, 2020 ; Adhikari et al, 2021 ; Banstola et al, 2021 ; Basheti et al, 2021 ; Bilgi et al, 2021 ; Gao et al, 2021 ; Guo et al, 2021 ; Gupta et al, 2021 ; Halperin et al, 2021 ; Kalkan Uğurlu et al, 2021 ; Kaplan Serin and Doğan, 2021 ; Keskin, 2021 ; Kuman Tunçel et al, 2021 ; Li et al, 2021 ; Mekhemar et al, 2021 ; Meng et al, 2021 ; Nishimura et al, 2021 ; Patelarou et al, 2021 ; Pavan et al, 2021 ; Pelaccia et al, 2021 ; Perissotto et al, 2021 ; Saeed and Javed, 2021 ; Safa et al, 2021 ; Song et al, 2021 ; Xiao et al, 2021 ; Xie et al, 2021 ; Yadav et al, 2021 ; Yang et al, 2021 ; Yin et al, 2021 ; Zhang et al, 2021a ; Zheng et al, 2021 ; Zhu et al, 2021 ). On the whole, 40 cross-sectional studies and 1 longitudinal study were included in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Studenti medicine pokazuju visoke skorove anksioznosti koji su čak i viši od skorova među opštom populacijom (36) jer se kod njih može javiti stigma u slučajevima kada žele da potraže pomoć stručnjaka, pa se zbog toga oslanjaju više na lične resurse. Rezultati istraživanja iz Njujorka (37) (38). Kod studenata iz Kine simptomi anksioznosti su bili izraženiji ako su njihovi uslovi školovanja tokom pandemije bili lošiji (39), što govori o njihovoj važnosti za mentalno zdravlje.…”
Section: Anksiozne Reakcije Studentske Populacije Tokom Pandemije Bol...unclassified